2007
DOI: 10.1242/dev.003103
|View full text |Cite
|
Sign up to set email alerts
|

Specification ofArabidopsisfloral meristem identity by repression of flowering time genes

Abstract: Flowering plants produce floral meristems in response to intrinsic and extrinsic flowering inductive signals. In Arabidopsis, the floral meristem identity genes LEAFY (LFY) and APETALA1 (AP1) are activated to play a pivotal role in specifying floral meristems during floral transition. We show here that the emerging floral meristems require AP1 to partly specify their floral identities by directly repressing a group of flowering time genes, including SHORT VEGETATIVE PHASE (SVP), AGAMOUS-LIKE 24 (AGL24) and SUP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
287
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 267 publications
(304 citation statements)
references
References 43 publications
13
287
3
1
Order By: Relevance
“…4 B and C). These results, together with the known function of SVP genes as suppressors of flowering and inflorescence development (30)(31)(32)(33), suggest that the three SVP genes work downstream of TAW1 to suppress SM identity. Using a two-component induction system, we confirmed that the induction of TAW1 transcription does indeed lead to the activation of the three SVP genes (Fig.…”
Section: Taw1 Is Expressed In the Meristem To Suppress The Transitionmentioning
confidence: 75%
“…4 B and C). These results, together with the known function of SVP genes as suppressors of flowering and inflorescence development (30)(31)(32)(33), suggest that the three SVP genes work downstream of TAW1 to suppress SM identity. Using a two-component induction system, we confirmed that the induction of TAW1 transcription does indeed lead to the activation of the three SVP genes (Fig.…”
Section: Taw1 Is Expressed In the Meristem To Suppress The Transitionmentioning
confidence: 75%
“…cytokinin pathway components) its target genes. We speculate that its interactions with partners in higher order complexes, and their interactions with chromatin modifiers, may determine its effect on gene expression, as is known for other transcription factor complexes (Sridhar et al, 2006;Liu et al, 2007;Smaczniak et al, 2012). The cumulative effects of these complexes on net target gene expression status culminates in a rice spikelet with a determinate floret with differentiated organs (Fig.…”
Section: Osmads1 Negatively Regulates Cytokinin Signaling In Florets mentioning
confidence: 90%
“…Total RNAs were isolated using the RNeasy RNA isolation kit (Qiagen) and reverse transcribed by the ThermoScript RT-PCR system (Invitrogen). Quantitative real-time PCR assays were performed in triplicate on a 7900HT Fast Real-Time PCR system (Applied Biosystems) using TUBULIN2 (TUB2) as an internal control as described previously (Liu et al, 2007). The efficiency of each pair of primers was determined based on its standard curve obtained from a series of 10-fold diluted template DNAs.…”
Section: Microarray Experiments and Data Analysismentioning
confidence: 99%